Effects of epidural anesthesia on I and II delivery stage and on a newborn - Čutura Neđo; Soldo Vesna; Ćurković Aleksandar; Tomović Branko; Mitrović Tanja (Vojnosanitetski Pregled)
Background/Aim. Epidural anesthesia (EA) is the most efficient method of pain reduction and its total elimination during delivery. The aim of this study was to establish an influence of EA on the first and the second part of delivery process, frequency of vacuum extractor and forceps appliance, and the effect of EA on the newborn. Methods. A total of 360 patients with EA were analyzed at delivery and 1 130 controls without EA. Both groups had vaginal delivery. In both groups deliveries were stimulated by 10 IU of oxytocin in 500 mL of crystalloid solvent, with 15-20 drops per minute. As anaesthetic, Bupivacain (0,25% or 0, 125%) was used by the 18 G catheters Braun and Wigon. Level of application was L2-L3 part of spine. Results. The results of this study indicate that deliveries with EA were shorter in duration, but also had much more vacuum extractor and forceps appliance (over 2.5 times) than those without EA. Apgar score was significantly higher in the experimental group with multiple deliveries. However, there was no significant deference between average Apgar score of newborns of patients with EA and that of newborns of patients without EA. Conclusion. Application of EA decreases duration of delivery, and has no any adverse effects on newborns.